2021
DOI: 10.3390/ijgi10110744
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Evolution of the Online Social Network after a Natural Disaster

Abstract: Social media has been a vital channel for communicating and broadcasting disaster-related information. However, the global spatiotemporal patterns of social media users’ activities, interactions, and connections after a natural disaster remain unclear. Hence, we integrated geocoding, geovisualization, and complex network methods to illustrate and analyze the online social network’s spatiotemporal evolution. Taking the super typhoon Haiyan as a case, we constructed a retweeting network and mapped this network a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…To find the more essential participants who deviated from the norm, we measured the complementary cumulative degree distribution of the out‐degree of the mentioned media (the complementary cumulative degree represents the probability that the degree value in the network is greater than k). It is generally agreed in the literature that the node degree distribution of crisis information networks regarding forwarding and citation behaviour follows a power law (Dong et al, 2018; Shen et al, 2022). In the news citation network pertaining to COVID‐19, we found that some high‐degree media had smaller complementary cumulative degree values than the power‐law distribution function curve.…”
Section: Measurement and Analysismentioning
confidence: 99%
“…To find the more essential participants who deviated from the norm, we measured the complementary cumulative degree distribution of the out‐degree of the mentioned media (the complementary cumulative degree represents the probability that the degree value in the network is greater than k). It is generally agreed in the literature that the node degree distribution of crisis information networks regarding forwarding and citation behaviour follows a power law (Dong et al, 2018; Shen et al, 2022). In the news citation network pertaining to COVID‐19, we found that some high‐degree media had smaller complementary cumulative degree values than the power‐law distribution function curve.…”
Section: Measurement and Analysismentioning
confidence: 99%
“…In order to understand the GDE nexus from a system perspective, and more deeply investigate the connections, functions, and interactions of grain, disaster, and economy systems, a complex network is introduced in this paper. Due to its unique strength in describing the interactions between the elements of complex systems [28], the complex network has received increasing research attention [29,30]. However, the complex network is unable to express the association of one subsystem with another in a complex system.…”
Section: Introductionmentioning
confidence: 99%